PENGEMBANGAN MEDIA PEMBELAJARAN APLIKASI SERENA BERBASIS ANDROID PADA MATEMATIKA MATERI DEBIT KELAS V SD - Saleh, Yopa Taufik; Nurfitriani, Meiliana; Febrian, Sharah (PGSD Universitas Muhammadiyah Cirebon, 2023)
Abstract The lack of supporting learning media makes it difficult for students to understand the discharge material so that it affects the work of various practice questions. This development and research aims to create a product in the form of an android-based learning media application that can be used in learning mathematics with discharge materials. This study uses the Research and Development method with the Borg and Gall model with 10 stages. This study used a simple random sampling technique which was carried out at SDN Karikil in class V students with a total of 47 people. The data analysis technique in this study used quantitative and qualitative descriptive statistical analysis techniques, and used data collection such as interviews, questionnaires and tests. The development of learning media for the Android-based Serena application has met the appropriate criteria. The results of this study showed a significant change, the experimental class got an average score of n-gain